Photoshop CS5 Essential Skills - Galer, Mark; Andrews, Philip (Focal Press, 2014)
Master Photoshop CS5 project-by-project! Using a celebrated combination of real world examples, step-by-step projects and professional advice, two internationally recognized authors and Adobe Photoshop Ambassadors guide you through this powerful software package so you can start creating your own works of art in no time. Broken into three parts to form a structured, self-study guide, Photoshop CS5: Essential Skills covers all the foundation skills to get you going, and then more advanced techniques to truly hone your image editing skills. A complete section of step-by-step imaging projects helps you practice your skills and learn how to create professional quality images. . Over 12 hours of high-definition movie tutorials . Full resolution project images in Raw, TIFF and JPEG file formats . Multilayered Image Files . More than 100 royalty-free stock images . Presets and Actions to fast-track your workflow.
Keywords: Adobe Photoshop